PERANAN GURU DALAM MEMBENTUK KARAKTER DISIPLIN SISWA KELAS VIIIF DI SMP NEGERI 18 PONTIANAK - Rogayyah, Syarifah; Khosmas, Khosmas; Budi, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was the teacher role in shaping the discipline of the eighth class F in the countryâ€™s first high school 18 pontianak. The sub problem in this research was how a teacherâ€™s role in giving direction, guiding, leader, motivatoin, evaluator. The analisys in study was Â with qualitative descriptive, role in directing are teacher always untructing students to come on time, teacher also play role in guiding students through the guindance programs the teacger has already done to provide guindance in all religious activities. Then the teacher has also been indtrumental in watching the students, with a notebook of abuses commited by student. The theacher role as a leader in wich teachers can be a good example for student and act according to the values that are applicable in school. The teachers role as motivation can be seen in the teachers presence give motivation and cousel to student who violate school rules of discipline. Then the teacher also had done his role as the evaluatorthat the teachers always assigned to each end of the learning and assessments are based on attitudes and result of the assigment given to students.Keyword: A character of student dicipline, a teachers role.